Flexible substrate based wideband polarization converter with extremely high polarization conversion ratio - Ismail Hossain; Mohammad Tariqul Islam; Norsuzlin Mohd Sahar; Abdulwadoud A. Maash; Haitham Alsaif; Mohamed S. Soliman; Md Samsuzzaman (Alexandria Engineering Journal)
In this article an anticipated reflection-mode cross-polarization converters (CPCs) are designed on a polydimethylsiloxane (PDMS) based flexible substrate operating in the GHz region. The proposed CPC metasurface comprises three layers where a flexible substrate is endwise between the resonating layer and ground layers. The converter can convert linear to circular and circular to cross-polarized waves at the frequency range of 5–8 GHz, as evidenced by the identical amplitude of Rxx and Ryx and a phase difference of 90°. More than 99 % of the polarization conversion ratio (PCR) was performed between the 6.75 and 9.07 GHz frequency range, while more than 80 % of the PCR was performed between the 6.0 and 10.73 GHz frequency range. The highest PCR values show nearly flawless energy conversion from an x-polarized incident wave to a y-polarized reflected wave. The PCR ratio of 80 % is achieved by this ultra-wideband linear-to-cross- and circular-to-cross-polarization converter. The anticipated converter's spectrum for all incidence angles between 0◦ and 60°. The PCR remained higher than 99 % over a wide incidence angle range to 60° without much performance degradation. The bending stability of the PDMS-based flexible substrate is also investigated up to 60°. The structure is fabricated on a flexible substrate, and the measured performance is compared with simulated results. Radar, antenna, and communications systems, as well as other cross-polarization converters, can utilize the transmitted wave's very high polarization purity result.